Apexification with mineral trioxide aggregate on post trauma right maxillary central incivus teeth - Masa, Maria Margaretha S. Nogo; Pratiwi, Dian Dwi; Cahyani, Febriastuti; Zubaidah, Nanik; Namira, Safa Marety; Wulandini, Raden Ajeng; Tanzil, Muhammad Iqbal; Oktaria, Wanda; Saraswati, Widya (Conservative Dentistry Journal, 2023)
Background: Trauma often occurs in the maxillary anterior teeth in both children and adults. This usually causes the pulp of a tooth whose root is not yet fully formed to experience necrosis, and the apex closure stops causing the apex to be wide and open. Apexification is a method to induce a calcified barrier in necrotic roots with open apex. Treatment with Mineral trioxide aggregate (MTA) can shorten treatment time and has a higher long-term success rate than using Ca(OH)2. Purpose: The aim of this report is to describe apexification cases using MTA on a non-vital right maxillary central incisor. Case: A 21-year-old male patient came to the Dental Conservation Clinic at Airlangga University Dental Hospital with complaints of broken and discolored front teeth. The tooth was broken after falling ± 10 years ago (2013) while playing football, it was swollen and painful, but in the last ± 1 year (2022) it has never hurt again. The patient's medical history revealed no systemic abnormalities. Objective examination of tooth 11 class IV ellis fracture, negative percussion and bite test, surrounding normal gingiva, no mobility. The radiographic appearance of tooth 11 shows a wide open apex and a radiolucency at the root tip. Vitality of non-vital teeth, Diagnosis of pulpal necrosis with asymptomatic apical periodontitis. Case Management: In this case, the treatment plan is endodontic treatment in the form of apexification with MTA material. The obturation technique was performed using warm thermoplastic (backfill) and accompanied by a fixed restoration using a fiber post and all porcelain crown with a good prognosis for patient care. Conclusion: Apexification with MTA with post and IPS Emax crown restoration is a good treatment option for immature right maxillary central incisor with open apex. The patient is satisfied because the teeth can return both aesthetically and functionally according to the stomatognathic system.